Potential differentiation of human amniotic epithelial stem and mesenchymal bone marrow cells into cardiomyocytes - Motamedi, Batool (2015)
Coronary artery disease (CAD) is the leading cause of cardiovascular mortality worldwide and stem cell transplantation is one of the approaches in the treatment of CAD (Leri et al., 2008; Laflamme and Murry, 2011).Realization of regenerative cardiac medicine is dependent on the availability of cardiomyocytes in sufficient numbers for transplantation. Bone marrow mesenchymal stem cells (BM-MSCs) have been used in clinical cell therapy and injecting BM-MSCS into mouse with Kaposi’s sarcoma resulted in reduced tumour. However the same cells have been reported to promote tumour growth when injected in mouse with osteosarcoma which also promoted pulmonary metastasis. The amnion is a simple epithelium resting on a connective tissue layer comprising of collagen fibers and fibroblasts. The amnion has two groups of stem cells. The first group are surface epithelial cells with pluripotent properties; the second group are stromal cells with mesenchymal stem cells (MSCs) properties in the underlying connective tissue of the amnion. Pluripotent cells are capable of giving rise to various body cell types similar to those of the three germ layers of the early embryo. MSCs have at least three primary characteristics: these cells grow as adherent cells in tissue culture dish; have a life span of 30 to 50 population doubling number and in vitro these cells could differentiate into osteoblasts, chondroblasts, and adipocytes. In view of the above amnion which form part of the placenta and discarded following child birth is therefore a useful biological material as it is a source of cells for transplantation. In the search for a source of cardiomyocytes for transplantation the present study investigates into the characteristics and potential of human amniotic epithelial cells (hAECs) to differentiate into cardiomyocytes. The characteristics and differentiation potential of the hAECs are concurrently compared with that of BM-MSCs, the gold standard in cell therapy. hAECs and BM-MSCs were isolated from the amniotic membrane and bone marrow, respectively and their cell surface antigens characterized based on flow cytometry, culture properties and colony formation. The proliferation rates of hAECs and BM-MSCs were calculated based on population doubling time, while adipogenic and osteogenic differentiation potentials were confirmed by the oil red O and alizarin red S staining methods, respectively. In addition, alkaline phosphatase (ALP) activity was determined using a colorimetric assay kit. The hAECs and BM-MSCs were then differentiated into cardiomyocytes in a cardiogenic medium containing 3µM 5-azacytidine. The differentiated cardiomyocyte were compared with normal cardiomyocytes by focusing on their specific protein expressions while their structural properties were determined by transmission electron microscopy. Results showed that both hAECs and BM-MSCs expressed MSCs factors. The expression of CD73, CD105, and CD90 in hAECs was 77.3%±4.9%, 78.3%±7.2% and 87.7%±3.1% respectively while in the BM-MSCs the expression for the same factor was 82%±4%, 80%±8.3% and 83.3%±2.9%, respectively. hAECs and BM-MSCs on the other hand did not express hematopoietic stem cell factors. The expression of CD34 and CD45in hAECs was 6%±1.1% and 5.5%±1.5% respectively while in the BM-MSCs expression for the same factor was 4.5%±0.5% and 5%±1%, respectively. No significant differences in mesenchymal and hematopoietic stem cells factors expression was observed between the two groups of cells. The low expression of CD34 and CD45 in the hAECs and BM-MSCs showed that these cells were not contaminated with cord blood or embryo or bone marrow hematopoietic cells. Results from the present study also demonstrated that the hAECs expressed embryonic stem cell markers where the expression of OCT4 in these cells was 73%±11% while in the BMMSCs the expression for the same marker was 19%±2%; there was thus a significant difference between the two cell types (p<0.001). From these data it can be deduced that the hAECs are pluripotent while the BM-MSCs are multi potent with the potential to differentiate into derivatives of two germ layers. Both hAECs and BM-MSCs could possibly differentiate into adipogenic cells as indicated by the positive Oil Red O staining (over 70% and 50% respectively). Both cell types also demonstrated the potential to differentiate into osteogenic cells as evidenced by positive alizarin red staining (over 35% and 55%, respectively) with significant difference (p<0.01) between the two cell types. hAECs one week after primary culture and BM-MSCs two weeks after primary culture formed colonies with alkaline phosphatase activities. The use of 5-Azacytidine at 3µM concentration demonstrated that both hAECs and BMMSCs could possibly differentiate into cardiomyocytes. Based on this observation on their differentiation potential the structural organization of both cell types were examined at the ultra-structural level. These differentiated cells showed initially the formation of unorganized myofibrils and subsequently to organized and parallel myotubes. The genotypes of these cells were determined by immunocytochemistry staining. The antibodies against alpha-actin, connexin43, N-cadherin, desmin, nestin and vimentin were used to identify differentiated cells. The induced hAECs and BM-MSCs expressed specific cardiomyocyte proteins in the form of alpha-actin (55% and 44% respectively) and connexin43 (80% and 70% respectively) which were similar to that of normal cardiomyocyte. The quantitative real-time RT-PCR indicated that there were no statistical significant differences between the expression of GATA-4, MLC-2a, MLC-2v, cTnI and connexin-43 in induced hBM-MSCs and hAECs with neonatal heart tissue. From the above result it can be concluded that the hAECs possess stem cells properties similar to that of BM-MSCs and express some pluripotent and embryonic markers at a level higher than BM-MSCs. In addition hAECs are similar to BM-MSCs where, both groups that of could differentiate into osteocyte and adipocyte; however, hAECs have a greater the tendency to differentiate into adipocyte, while BM-MSCs have a greater the tendency to differentiate into osteocyte. When these cells are induced into cardiomyocyte both hAECs and BM-MSCs showed similarities to cardiomyocytes such as the formation of unorganized myofibrils to organized, parallel myotubes and expressed cardiomyocyte specific genes and protein markers. Hence, hAECs could be a suitable substitute in heart cell transplantation instead of BM-MSCs.